Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1038/sj.onc.1209958
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new class of PAX3-FKHR target promoters: a role of the Pax3 paired box DNA binding domain

Abstract: Alveolar rhabdomyosarcoma (aRMS), an aggressive skeletal muscle cancer, carries a unique t(2;13) chromosomal translocation resulting in the formation of a chimeric transcription factor PAX3-FKHR. This fusion protein contains the intact DNA-binding domains (PD: paired box binding domain; HD: paired-type homeodomain) of Pax3 fused to the activation domain of FKHR. Cells expressing Pax3 and PAX3-FKHR show vastly different gene expression patterns, despite that they share the same DNA-binding domains. We present e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 42 publications
2
35
1
Order By: Relevance
“…In contrast, a previous study showed that PAX3-FKHR can transactivate myogenin independent of MyoD. 60 Moreover, a recent study demonstrated that PAX3-FKHR activates MyoD expression, but at the same time attenuates the MyoD-mediated terminal myogenic program. 15 Our data demonstrates that the restoration of PAX3-FKHR activity mediated induction of MyoD by dnAKT is incompetent in gene activation function in ARMS grown in DM, supporting that PAX3-FKHR activity mediated simultaneous induction and inhibition of MyoD regulated the myogenic program.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, a previous study showed that PAX3-FKHR can transactivate myogenin independent of MyoD. 60 Moreover, a recent study demonstrated that PAX3-FKHR activates MyoD expression, but at the same time attenuates the MyoD-mediated terminal myogenic program. 15 Our data demonstrates that the restoration of PAX3-FKHR activity mediated induction of MyoD by dnAKT is incompetent in gene activation function in ARMS grown in DM, supporting that PAX3-FKHR activity mediated simultaneous induction and inhibition of MyoD regulated the myogenic program.…”
Section: Discussionmentioning
confidence: 69%
“…Khan et al (1999) reported similar results using expression arrays. PAX3-FKHR has also been shown to transactivate myogenin directly, independent of MyoD (Zhang and Wang, 2007). Therefore, it is possible that PAX-FKHR also activate myogenin directly during ARMS formation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these experiments support the hypothesis that one of the oncogenic functions of PAX3/FKHR is to block terminal differentiation. Furthermore, they suggest that the cellular background has a profound effect on target genes bound and activated by PAX3 and/or that the target gene spectra of PAX3 and PAX3/ FKHR differs (Zhang and Wang, 2006).…”
Section: Pax3/fkhr Promotes Arms Cell Survivalmentioning
confidence: 99%